Adult Education determinant of children’s education - Neagu, Gabriela (Formazione & insegnamento, 2014)
Adult education is a priority issue addressed in terms of personal and professional training to promote socio-cultural integration. This paper, given the context in which it is drawn, suggests a perspective for the analysis of adult education, namely, that the education of adults, regardless of the forms it takes, can favorably influence a new generation of lifelong learners. Based on statistical data from a research carried out in either with the entire adult population in Romania and with specific segments of the population – the population of school teachers – we reveal how a series of cultural and educational activities undertaken by adults together with their children, has impact on attitudes, behaviors, values exhibited by adults; moreover, these values are taken by children and have a significant impact on the education of the latter.